?MEDIAN LETHAL CONCENTRATION OF COPPER TO GOLDFISH CARASSIUS AURATUS LINNAEUS - HOSSAIN, M.A.; SHARIFF, M.; LAW, A.T.; PATlMAH, I. (Biological Sciences - PJSIR, 1995)
This study was undertaken to determine acute toxicity level (median lethal concentration) of copper to goldfish Carassius auratus Linnaeus, a freshwater cyprinid. The experiment was conducted in filtered (mesh size I urn) freshwater having total hardness 34.2 (as CaC03) in a static condition. Copper sulphate (CuS04 5HP) was used as a source of copper. The LCso values of copper were determined from probit values of cumulative mortality percentage against exposure concentrations (dose response) using simple linear regression model Y =a + bX. The LCso values of copper to goldfish (10.5 ± 1.43 g) were determined as 0.44 ± 0.06, 0.36 ±0.04,0.20 ±0.03,0: 19 ±0.02,0.15 ± 0.02 and 0.14 ± 0.02 ppm for 12,24,48,72,96 and 120 hr. respectively.